Our Futures. Te Pae Tawhiti. The 2013 census and New Zealand's changing population - Hawke, G; Bedford, R; Kukutai, T; McKinnon, M; Olssen, E; Spoonley, P (The Royal Society of New Zealand, 2014)
Our Futures: Te Pae Tawhiti brings together data and analysis from the 2013 census and other sources, together with input from a wide range of researchers, to provide evidence-based pointers to the future of New Zealand society. It covers seven key themes: diversity, population change, tangata whenua, migration, households and families, regional variation, and work.